ANALYSIS AND PERCEPTION OF THE COSTS OF CORPORATE GOVERNANCE PRACTICES: A CASE STUDY - Trindade, Luana Zanetti; Bialoskorski Neto, Sigismundo (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
In order to improve the efficiency and transparency of credit unions, the Central Bank of Brazil has diagnosed the characteristics of governance and defined a range of best practices. The objective is to analyze the costs of compliance and disclosure of practices of corporate governance and the perception of these costs by the members of a cooperative. It was developed a case study at a credit union, in which was found that these costs represent 0.3205% of the total of organization`s assets. These costs can be considered high, as they are near of cooperative`s profitability, which is 0.38%. In addition, these costs represent 8.6% of administrative expenses. In the questionnaires applied to the members, it was possible to observe that although the costs of compliance and disclosure of practices of governance are considered high by the management of the credit union, its members may not be aware of these costs. Much of them can notice the efficiency of management and also that corporate governance is an investment for the organization.